2020
DOI: 10.3389/fnmol.2020.552073
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay Between Beta-Amyloid 1–42 (Aβ1–42)-Induced Hippocampal Inflammatory Response, p-tau, Vascular Pathology, and Their Synergistic Contributions to Neuronal Death and Behavioral Deficits

Abstract: Alzheimer's disease (AD), the most common chronic neurodegenerative disorder, has complex neuropathology. The principal neuropathological hallmarks of the disease are the deposition of extracellular β-amyloid (Aβ) plaques and neurofibrillary tangles (NFTs) comprised of hyperphosphorylated tau (p-tau) protein. These changes occur with neuroinflammation, a compromised blood-brain barrier (BBB) integrity, and neuronal synaptic dysfunction, all of which ultimately lead to neuronal cell loss and cognitive deficits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 119 publications
(145 reference statements)
2
13
0
Order By: Relevance
“…Regarding neuroinflammation, we found that a single administration of Aβ 1–42 stimulated neuroinflammatory processes, causing a significant increase in the densities of activated microglia and hyperreactive astrocytes. In line with our observations, several in vivo experiments have demonstrated the neuroinflammation-inducing effects of Aβ fibrils and oligomers injected into the brain tissue in different experimental models [ 93 , 94 , 95 ]. This neuroinflammatory environment may affect adult neurogenesis either positively or negatively [ 11 , 12 , 96 , 97 , 98 , 99 , 100 , 101 ].…”
Section: Discussionsupporting
confidence: 89%
“…Regarding neuroinflammation, we found that a single administration of Aβ 1–42 stimulated neuroinflammatory processes, causing a significant increase in the densities of activated microglia and hyperreactive astrocytes. In line with our observations, several in vivo experiments have demonstrated the neuroinflammation-inducing effects of Aβ fibrils and oligomers injected into the brain tissue in different experimental models [ 93 , 94 , 95 ]. This neuroinflammatory environment may affect adult neurogenesis either positively or negatively [ 11 , 12 , 96 , 97 , 98 , 99 , 100 , 101 ].…”
Section: Discussionsupporting
confidence: 89%
“…Similarly, in a mostly preclinical cohort, pTau does not directly reflect the regional accumulation of neurofibrillary tangles and is probably, at least in part, indicative of a neuronal response to the deposition of β‐amyloid proteins. 13 , 52 As a result, it is likely that some of our DWI associations with pTau are artificially inflated by underlying amyloid pathology. Third, we did not consider the presence of WM hyperintensities (WMH) in our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…We also report no acute Aβ 1‐42 ‐induced alteration in GluN2A subunit density within the mouse hippocampus ( 39 ), but chronic exposure resulted in downregulated subunit levels secondary to reduced neuronal labeling ( 31 ). In the mouse CA1 subregion 3‐days post‐Aβ 1‐42 injection astrogliosis is high and extended throughout the region, but at 3‐days post‐injection, increased GFAP density and astrocytes with activated morphology are localized to the injection site only ( 62 ). In the human CA1 subfield we did not detect GluN2A on neurons and the upregulation of GluN2A is associated with increased astrogliosis, the characteristic feature of AD and other neurodegenerative disorders ( 63 , 64 , 65 ), and increased expression of the subunit is localized to GFAP positive cells and processes.…”
Section: Discussionmentioning
confidence: 99%